Transfecting RAW264.7 Cells with a Luciferase Reporter Gene - Cheung, Sylvia T. (J Vis Exp, 2015)
Transfection of desired genetic materials into cells is an inevitable procedure in biomedical research studies. While numerous methods have been described, certain types of cells are resistant to many of these methods and yield low transfection efficiency(1), potentially hindering research in those cell types. In this protocol, we present an optimized transfection procedure to introduce luciferase reporter genes as a plasmid DNA into the RAW264.7 macrophage cell line. Two different types of transfection reagents (lipid-based and polyamine-based) are described, and important notes are given throughout the protocol to ensure that the RAW264.7 cells are minimally altered by the transfection procedure and any experimental data obtained are the direct results of the experimental treatment. While transfection efficiency may not be higher compared to other transfection methods, the described procedure is robust enough for detecting luciferase signal in RAW264.7 without changing the physiological response of the cells to stimuli.